Dual Active Sites on Molybdenum/ZSM‐5 Catalyst for Methane Dehydroaromatization: Insights from Solid‐State NMR Spectroscopy. Issue 19 (6th April 2021) - Gao, Wei; Qi, Guodong; Wang, Qiang; Wang, Weiyu; Li, Shenhui; Hung, Ivan; Gan, Zhehong; Xu, Jun; Deng, Feng
Abstract: Methane dehydroaromatization (MDA) on Mo/ZSM‐5 zeolite catalyst is promising for direct transformation of natural gas. Understanding the nature of active sites on Mo/ZSM‐5 is a challenge for applications. Herein, using 1 H{ 95 Mo} double‐resonance solid‐state NMR spectroscopy, we identify proximate dual active sites on Mo/ZSM‐5 catalyst by direct observation of internuclear spatial interaction between Brønsted acid site and Mo species in zeolite channels. The acidic proton–Mo spatial interaction is correlated with methane conversion and aromatics formation in the MDA process, an important factor in determining the catalyst activity and lifetime. The evolution of olefins and aromatics in Mo/ZSM‐5 channels is monitored by detecting their host–guest interactions with both active Mo sites and Brønsted acid sites via 1 H{ 95 Mo} double‐resonance and two‐dimensional 1 H– 1 H correlation NMR spectroscopy, revealing the intermediate role of olefins in hydrocarbon pool process during the MDA reaction. Abstract : The bifunctional acidic proton‐carburized Mo active site in Mo/ZSM‐5 zeolite was revealed by probing their spatial proximity using double‐resonance solid‐state NMR spectroscopy. The spatial interaction of the dual site governs the activity of the catalyst for MDA reaction.